2020
DOI: 10.1002/ejoc.202000394
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation of Electron‐Deficient Vicinal Substituted Alkenes: Regio‐ and Stereoselectivity

Abstract: The halogenation of electron‐deficient vicinal substituted alkenes leads mainly to the mixture of regio‐ and stereoisomers of monohalogenated derivatives. Their ratio depends on the stability of the intermediate anionic complex and is determined by properties of both electron‐withdrawing groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Other convenient brominating reagents such as 1,2-dipyridiniumditribromide-ethane (DPTBE) or HBr in the presence of oxone were tested with ethyl sorbate. In contrast to the experiments using molecular bromine, in these cases the formation of ethyl 4,5-dibromohexenoate 6b as a principal reaction product was accompanied by the significant formation of isomeric 2,3-dibromoenoate 7b: its amounts were reached by 33 % (Table 1, entries 11,12).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Other convenient brominating reagents such as 1,2-dipyridiniumditribromide-ethane (DPTBE) or HBr in the presence of oxone were tested with ethyl sorbate. In contrast to the experiments using molecular bromine, in these cases the formation of ethyl 4,5-dibromohexenoate 6b as a principal reaction product was accompanied by the significant formation of isomeric 2,3-dibromoenoate 7b: its amounts were reached by 33 % (Table 1, entries 11,12).…”
Section: Resultsmentioning
confidence: 70%
“…The syntheses of bromoenoates described so far are based on the commonly used methods, namely bromination -dehydrobromination of parent compounds by molecular bromine or different organobromine compounds as halogenating reagents. [11] As a continuation of our research in this field, [12] here we report an efficient synthetic procedure for the bromination of dienoates. Depending on the reaction conditions, we prepared mono-and dibromodienoates and their precursors in good to excellent chemo-and stereoselectivity.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It should be noted that in one of the first articles the structure of dehydrobromination product was erroneously determined as 3‐bromo‐4,4,4‐trifluorocrotonate [51] . The complete and confident proof for the structure of this derivative was published recently [61] …”
Section: Aza‐michael Reaction With Pull‐pull Enoatesmentioning
confidence: 99%
“…[51] The complete and confident proof for the structure of this derivative was published recently. [61] To test whether the starting bromoenoate 52 can react as Michael acceptor, this substrate was treated with secondary amine under classical and hyperbaric conditions. It was found that the ester Z-52 a reacted with morpholine in ethanol under reflux to afford βamino ester 53 as a sole reaction product (Scheme 21).…”
Section: Conjugate Nucleophilic Addition To β-Trifluoromethyl Enoatesmentioning
confidence: 99%